Instability of the Atlantic overturning circulation during Marine Isotope Stage 3. Issue 12 (20th June 2014) - Zhang, Xiao; Prange, Matthias; Merkel, Ute; Schulz, Michael
Abstract Variations in the strength of the Atlantic meridional overturning circulation (AMOC) were involved in the occurrences of Dansgaard‐Oeschger (D‐O) events during Marine Isotope Stage 3 (MIS3). The stability of the AMOC to North Atlantic freshwater perturbations is studied using a comprehensive climate model under MIS3 boundary conditions. An AMOC stability diagram constructed from a series of equilibrium freshwater perturbation experiments reveals a highly nonlinear dependence of AMOC strength on freshwater forcing. The MIS3 baseline state is remarkably unstable with respect to minor perturbations. The global climate signal associated with a change in AMOC strength is consistent with a transition from an interstadial to a stadial state including an annual mean surface air temperature drop of 8 K in central Greenland. We suggest that minor freshwater perturbations in the hydrologic cycle, e.g., related to ice sheet processes, had the potential to trigger D‐O‐type climate shifts associated with a threshold in the atmosphere‐ocean system.